Laboratory Experiment To Determine Major Factors Controlling Landslides Triggered by Rising of Ground Water Level - Abdul Rahman, Nurul Liyana ‘Izzati (Universiti Teknologi PETRONAS, 2020)
Landslide is the most devastating hazard in Malaysia apart from flood. It is because the aftermath of the landslide is it pose fatalities and also could ruin any existing structures and hallmark in its route. The occurrence of landslide is very common in Malaysia every year especially during monsoon seasons. There are various factors that could contribute to the occurrence of the slope failures, and rainfall is one of the inevitable triggers particularly in tropical countries such as Malaysia. Hence, this paper is intended to focus on the nature of rainfall activated landslides, the rise of the groundwater level from the bottom of the slope which would lead to slope failures due to pore pressure evolution and the impact of rainfall infiltration. The study is examined in a fabricated model for work validation to ensure that it works on natural soil slope. The type of soil used was sandy silt. From the observation, the conclusion can be made as the groundwater table rises due to the rainwater infiltration. Soil with high permeability enables higher rate of rainwater to reach the groundwater table and cause groundwater level to rise faster. Quick rise of groundwater level may trigger a landslide. Thus, this landslide can be mitigated by control the groundwater level by adopting groundwater withdrawal system in laboratory experiment.